Knowledge, attitudes, and practices regarding Rift Valley fever and West Nile fever among livestock owners and health professionals in selected districts of the Afar Region, Northeast Ethiopia - Jemberu Alemu Megenas; Mengistu Legesse Dadi; Tesfu Kassa Mekonnen; James W. Larrick; Gezahegne Mamo Kassa (Veterinary Research Notes, 2024)
Objectives: East Africa is a hotspot for newly emerging arboviral diseases. In nations with limited resources like Ethiopia, outbreaks of vector-borne diseases can overwhelm healthcare systems. This study aimed to evaluate the knowledge, attitudes, and practices of health professionals, and livestock owners in selected areas of the Afar region. A cross-sectional study was employed between June 2021 and April 2022, using questionnaires, key informant interviews, and focus group discussions as data collection tools. Materials and Methods: A total of 150 (60 livestock owners, 40 animal health workers and para-veterinarians, and 50 public health professionals) participated in the study. Results: Of the participants, 29.3% (44/150) perceived zoonotic diseases to be transmitted through the consumption of food of animal origin or mosquito bites. More than half (63.3%, 95/150) of the participants had any feeling of insecurity regarding infection by Rift Valley fever (RVF), West Nile fever, or other zoonotic diseases. Animal health workers had higher (27.3±10.9) mean scores of knowledge of RVF, West Nile fever, and another zoonotic disease than public health professionals and livestock farmers/owners at p < 0.01. A statistically significant difference in mean scores was also observed among the educational status groups: illiterate, primary education (grades 1–8), and secondary and above (grades 9+). The mean practice scores were higher in the Amibara district (16.9 ± 6.4) compared to the Haruka district, with a p-value of 0.000. Conclusion: The present study found substantial knowledge gaps, a low level of risk concern, and high behavioral practices regarding zoonotic diseases. Community education and awareness programs need to be developed, and further investigations into the prevalence and risk factors for zoonosis in such settings should be conducted to identify intervention targets. [Vet. Res. Notes 2024; 4(10.000): 89-99]